Effectiveness of Intergovernmental Grants: A Systematic Literature Review - Fitriadi, Fitriadi; Haliah, Haliah; Nirwana, Nirwana; Kusumawati, Andi (International Ecsis Association, 2024)
This article aims to analyze the effectiveness of intergovernmental grants. Although the government has provided grants to various entities, including intergovernmental ones, there has yet to be a comprehensive study that illustrates the effectiveness of these intergovernmental grants. Systematic Literature Review and meta-analysis are used to answer the research question. There are 199 articles found using the keyword